Assessment and Technology: Mapping Future Directions in the Early Childhood Classroom - Neumann, Michelle M.; Anthony, Jason L.; Erazo, Noé A.; Neumann, David L. (Frontiers in Education, 2019)
The framework and tools used for classroom assessment can have significant impacts on teacher practices and student achievement. Getting assessment right is an important component in creating positive learning experiences and academic success. Recent government reports (e.g., United States, Australia) call for the development of systems that use new technologies to make educational assessment more efficient and useful. The present review discusses factors relevant to assessment in the digital age from the perspectives of assessment for learning (AfL) and assessment of learning (AoL) in the early childhood classroom. Technology offers significant avenues to enhance test administration, test scoring, test reporting and interpretation, and link with curriculum to individualize learning. We highlight unique challenges around issues of developmental appropriateness, item development, psychometric validation, and teacher implementation in the use of future assessment systems. However, success will depend upon close collaboration between educators, students, and policy makers in the design, development, and utilization of technology-based assessments.